Siklus Hidup Spodoptera frugiperda Dengan Pemberian Pakan Kangkung dan Daun Bawang di Laboratorium - Ichsan Luqmana Indra Putra; Nanda Dwi Martina (Jurnal Ilmu Pertanian Indonesia, 2021)
Spodoptera frugiperda was found to have entered Indonesia and damaged maize crops. There is a concern that climate change in Indonesia will cause these pests to migrate to other crops besides corn, such as kale and leeks. This research was conducted to observe the life cycle of S. frugiperda with feed treatment of kale leaves, leeks and corn leaves as a control. The larvae came from corn fields that were infested by S. frugiperda and were cultured in the laboratory. The variables observed were larva length, head diameter, pupa length, number of eggs, sex ratio, and time to complete one cycle. The life cycle of S. frugiperda varies between 37 and 47 days. Kale leaf feed is a good feed for the growth of S. frugiperda compared to the other two feeds, while corn leaf is good in fecundity. Keywords: corn, fecundity, growth, life cycle, sex ratio